ANALYSIS OF BIOLOGICAL ACTIVITY AND GAS CHROMATOGRAPHY-MASS SPECTROMETRY STUDY OF CONVENTIONAL EXTRACTION OF VITEX NEGUNDO LINN. LEAVES - Fatema, Samreen; Ubale, Milind; Farooqui, Mazahar; Arif, Pathan Mohd (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The main objective of the present work is to carry out the biological activity, gas chromatography-mass spectrometry (GC-MS) studies for the possible compounds present in Vitex negundo. Methods: The aqueous extract of V. negundo Linn. was screened for biological activities such as antimicrobial, antituberculosis (TB), antimalarial, and antioxidant activities. The GC-MS analysis was carried out. Results: The result shows that leaf extract is effective against Escherichia Coli and Bacillus subtitus while negative results for anti-TB and anti-malarial activity. The antioxidant activity of the leave extract is excellent. Conclusion: The compounds present in the leaf extract of V. negundo are responsible for possessing the biological activity.